WISE‐NVSS selected obscured and ultraluminous quasars with compact radio jets. Issue 9 (17th November 2021) - Patil, Pallavi; Whittle, Mark; Nyland, Kristina; Lonsdale, Carol; Lacy, Mark; Kimball, Amy; Lonsdale, Colin; Peters, Wendy; Clarke, Tracy E.; Efstathiou, Andreas; Giacintucci, Simona; Kim, Minjin; et al.
Abstract: Active galactic nucleus (AGN) feedback at z ∼ 1 − 3 is believed to take place in the presence of thick columns of gas and dust, leading to heavily obscured systems that are challenging to detect at optical and X‐ray wavelengths but are transparent at radio and mid‐IR (MIR) wavelengths. MIR color diagnostics using the widefield infrared space explorer (WISE) observations can identify the most luminous and heavily obscured AGNs, which are believed to represent a transient phase of rapid massive black hole growth. By combining both mid‐IR and radio diagnostics, we have identified a sample of 155 ultraluminous and obscured quasars ( 0.4 < z < 3 ) selected to have extremely red mid‐IR colors in WISE and compact, bright ( > 7 mJy) radio emission in the NRAO VLA Sky Survey (NVSS) and Faint Images of the Radio Sky at Twenty‐one centimeters (FIRST). High‐resolution very large array (VLA) imaging has revealed compact source morphologies on angular scales < 0 . 2 ″ (1.7 kpc at z ∼ 2 ) for the majority of our sources. Broadband radio spectra of the entire sample, constructed from our 10 GHz VLA observations and archival radio data show that 63% of the sample has peaked or curved spectral shapes consistent with those typically seen in young radio AGN (e.g., gigahertz peaked spectrum [GPS] and compact steep spectrum [CSS] sources). Overall, our sample is consistent with a population of recently triggered, young radio jets caught in a unique evolutionary stage in which they reside in a dense interstellar medium (ISM).